The continuous rise – during economic growth, the COVD-19 pandemic and conflict – in the adoption of labor-saving agricultural technologies in Myanmar - Minten, Bart; Sabai, Moe (2023)
The presentation was help virtually on November 7, 2023 at 9:30 AM Myanmar Standard Time. This is an output of the Myanmar Strategy Support Program, funded through the Feed the Future Initiative conducted jointly with US Agency for International Development, International Food Policy Research Institute, and Michigan State University.